Clinical and Histopathological Assessment of Hepatocellular Injury in Pediatric Hepatitis A and E Infections: Insights from a Comparative Study - Neelam Faryad, Iram Khan, Tabassum Bashir, Nasir Khan, Abid Ali Ranjha, Saleem Adil (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Acute hepatocellular injury caused by hepatitis A and E represents a significant burden in pediatricpopulations, yet comparative histopathological data remains scarce. Present investigation aimedto characterize clinical and histopathological features of pediatric hepatitis A versus E infectionswithin a prospective cohort, employing rigorous comparative analysis. A total of 120 children with